Selaginella extracts extend lifespan and mitigate oxidative stress in Caenorhabditis elegans - Chen, Xueqing; Yan, Bingjian; Wu, Yingmei; Quan, Wenjing; Liu, Yu; Huang, Yaning; Shao, Yinjie; Wang, Yuan; Zhou, Qi; Liu, Yifei; Liu, Songlin; Wang, Jin; et al. (Frontiers in Pharmacology, 2025)
IntroductionSelaginella species hold a traditional place in medicine and cosmetics, but their potential to extend lifespan and the underlying bioactive compounds remain inadequately investigated. This study aims to systematically evaluate the anti-aging properties of diverse Selaginella extracts and to identify the key bioactive components and mechanisms involved.MethodsWe collected 23 Selaginella samples from 13 different provinces across China to assess their geographical influence. Two representative methanol extracts, S4 (high in amentoflavone) and S16 (low in amentoflavone), were selected for in-depth evaluation using the Caenorhabditis elegans model. We employed lifespan assays, stress resistance tests, and comparative transcriptomics to analyze the effects on longevity, and pathway modulation.ResultsBoth S4 and S16 extracts significantly extended the lifespan of C. elegans under normal conditions and modulated conserved longevity pathways, including MAPK and FOXO signaling, with daf-16 and egl-8 emerging as key hub genes. Amentoflavone was identified and validated as a critical bioactive component, which alone extended lifespan by 63.81% and enhanced stress resistance. Mechanistically, amentoflavone promoted the nuclear translocation of DAF-16 and up-regulated the expression of antioxidant genes (e.g., sod-3, gst-3/4, hsp-16.48/12.6), leading to a significant reduction in intracellular ROS levels.DiscussionOur findings demonstrate that Selaginella extract and its key component, amentoflavone, delay aging primarily by activating the DAF-16/FOXO transcription factor and bolstering the antioxidant defense system. This study not only highlights amentoflavone as a major contributor to the lifespan-extending effects of Selaginella but also underscores the potential of these natural compounds as promising agents for healthy aging.